Comprehensive Assessment of Cannabidiol and HU308 in Acute and Chronic Colitis Models: Efficacy, Safety, and Mechanistic Innovations - Dinesh Thapa; Mohan Patil; Leon N Warne; Rodrigo Carlessi; Marco Falasca (Cells)
Cannabinoids are emerging as promising treatments for inflammatory diseases such as ulcerative colitis. Specifically, cannabinoid 2 (CB2) receptors, which are upregulated during inflammation, have been distinctively linked to anti-inflammatory and analgesic effects. HU308, a synthetic cannabinoid developed to activate CB2 receptors selectively, aims to minimize unwanted off-target side effects. This study evaluated the effectiveness of both cannabidiol (CBD) and HU308 in mouse models of dextran sodium sulphate (DSS)-induced colitis, which mimic the acute and chronic phases of ulcerative colitis. Mice were treated with DSS in drinking water (four percent for the acute model and one to two percent for the chronic model) to induce colitis, as indicated by increased disease activity index (DAI) scores and inflammatory markers. Treatment with 60 mg/kg of CBD, but not lower doses, significantly reduced colitis symptoms, such as inflammation, cytokine levels, and MPO activity, while also normalizing glucagon-like peptide-1 (GLP-1) levels. HU308 showed comparable efficacy to high-dose CBD (60 mg/kg) but at a much lower dose (2.5 mg/kg), without observable toxicity. HU308 effectively normalized DAI scores, colon inflammation, ammonia levels, and GLP-1 expression in both colitis models. These results suggest that both CBD and HU308 are promising treatments for ulcerative colitis. However, HU308 demonstrates enhanced therapeutic potential by achieving similar outcomes at a fraction of the dose required for CBD, reducing the risk of off-target side effects. The ability of HU308 to modulate GLP-1, a biomarker of gut endocrine function, further underscores its promise as a novel treatment option.